The ANALISIS YURIDIS PERBARENGAN PERBUATAN (CONCURSUS REALIS) DALAM TINDAK PIDANA PERSETUBUHAN YANG DILAKUKAN ANAK TERHADAP ANAK (STUDI PUTUSAN NOMOR 44/PID/SUS-ANAK/2022/PN/MKS) - Farida, Abd. Rahma Syarif; Ivan Natsir, Nanda (Fakultas Hukum Universitas Mataram, 2024)
ABSTRACT This study aims to examine the judge's basic considerations in imposing criminal punishment and how the criminal punishment is applied to concurrent criminal acts (concursus realis) in the crime of sexual intercourse committed by a child against a child in Decision Number: 44/Pid/Sus-Anak/2022/PN/Mks. The type of research used is normative research. The results of this study indicate that the actions of child perpetrators, besides meeting the elements of intercourse in Article 81 paragraph (2), also met the elements of concurrent acts in Article 65 of the Criminal Code. The implementation of the criminal sentence given by the judge is much lighter than the prosecutor's demands. The judge provides an opportunity for the child defendant to be able to rehabilitate himself and avoid repeating acts that violate the law. The judge should utilize his